Severe and Rare Case of Human Dirofilaria repens Infection with Pleural and Subcutaneous Manifestations, Slovenia - Helena Biasizzo; Barbara Šoba; Frosina Ilovski; Matevž Harlander; Matej Lukin; Olga Blatnik; Matjaž Turel; Matevž Srpčič; Izidor Kern; Bojana Beović (Emerging Infectious Diseases, 2022)
We report a case of human Dirofilaria repens infection in a woman in Slovenia who had concomitant pleural and subcutaneous manifestations of the infection. This case report illustrates the clinical course of a severe symptomatic parasitic infection that had multisystemic manifestations.